All-component comprehensive utilization method for leaching residues of laterite-nickel ore high-pressure acid leaching process

Through granulation and sintering, blast furnace smelting, cold quenching and grinding, the comprehensive utilization of the leaching slag of the leaching slag of the laterite nickel ore high pressure acid leaching process has been achieved, solving the problems of low efficiency and low comprehensive recycling rate in the existing technology, and achieving large-scale industrial application and 100% resource utilization of slag.

CN119876587AActive Publication Date: 2025-04-25CENT SOUTH UNIV

Patent Information

Application Number
CN202510383522.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-28
Publication Date
2025-04-25
Estimated Expiration
2045-03-28

AI Technical Summary

Technical Problem

The prior art has problems such as inefficient and high consumption, low comprehensive recycling rate and difficulty in large-scale industrial application when treating leaching slags from laterite nickel ore.

Method used

By granulating and sintering the laterite nickel ore high-pressure acid leaching process, iron slag containing coke powder, flux and rebate, sintered ore and sulfur dioxide flue gas is obtained, which is used to prepare sulfuric acid and return to the process; the sintered ore is smelted with coke and slag agent through blast furnace to obtain molten iron and slag, and granulated slag powder is prepared by cold quenching and grinding; finally, the granulated slag powder, granulated slag and neutralized tailings are mixed as backfillers.

Benefits of technology

The large-scale and efficient comprehensive utilization of the leaching slag of the laterite nickel ore high-pressure acid leaching process has been achieved, which has reduced the cost of purchasing sulfuric acid raw materials, reduced energy consumption, achieved 100% resource utilization of the slag, and improved the performance of the backfiller.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119876587A_ABST
    Figure CN119876587A_ABST
Patent Text Reader

Abstract

The invention discloses an all-component comprehensive utilization method for leaching residues of a laterite-nickel ore high-pressure acid leaching process, and belongs to the technical field of solid waste resource utilization. The method comprises the following steps: granulating and sintering the iron-containing slag of the laterite-nickel ore high-pressure acid leaching process and raw materials containing coke powder, a flux and return mine to obtain sintered ore and sulfur dioxide flue gas; sulfur dioxide is used for preparing sulfuric acid and returned to the laterite-nickel ore high-pressure acid leaching procedure; smelting the sintered ore, coke and a slag modifier through a blast furnace to obtain molten iron and slag; the molten slag is subjected to cold quenching, and granulated molten slag is obtained; and after being ground, part of the granulated slag is mixed with the granulated slag and auxiliary materials containing an alkali activator and tailings in the laterite-nickel ore high-pressure acid leaching process to serve as a backfill material. By means of the method, low-consumption, efficient and large-scale all-component comprehensive utilization of the leaching residues of the laterite-nickel ore high-pressure acid leaching process can be achieved, 100% resource utilization of the residues is completed, and the method has considerable industrial popularization potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for comprehensive utilization of all components of leached residues from a high-pressure acid leaching process of laterite nickel ore, and belongs to the technical field of comprehensive utilization of metallurgy and industrial solid wastes. Background Art

[0002] Nickel is an important industrial metal, widely used in stainless steel, nickel-based alloys and ternary cathode materials. Technological progress and changes in market demand in the new energy industry have driven the rapid growth of nickel market demand. With the increasing depletion of sulfide nickel ore resources, laterite nickel ore has gradually become the main source of nickel extraction. Laterite nickel ore is usually divided into limonite layer, clay layer and saprolitic layer. The limonite layer is suitable for hydroprocessing, accounting for 65%~75%; the saprolitic layer is suitable for pyroprocessing, accounting for 15%~25%; the clay layer accounts for about 10% and can be treated by hydroprocessing or pyroprocessing. In hydroprocess smelting, high pressure acid leaching (HPAL) technology has become the mainstream choice due to its advantages such as low carbon emissions, low energy consumption, high comprehensive recovery rate of nickel and cobalt metals, and mature technology. However, for every ton of nickel metal product produced, up to 120 tons of leaching slag will be produced, including acid leaching slag, iron and aluminum removal slag and neutralization tailings. Among them, the acid leaching slag with the largest slag volume and the iron removal aluminum slag with the second largest slag volume contain rich iron and a large amount of silicon, aluminum, calcium, magnesium, sulfur and other components, and have extremely high resource recovery and utilization value. The neutralization tailings mainly composed of calcium sulfate salts have a relatively low recycling and utilization value. At present, for the effectiveness of the treatment method and economic considerations, most companies mainly adopt direct storage for the three, which not only causes serious waste of resources, but also heavy metal ions such as chromium, nickel, and cobalt in the slag may cause serious safety hazards to the ecological environment. Therefore, the harmless and resource-based treatment of HPAL slag is imminent.

[0003] At present, the resource utilization of leaching residue from high-pressure acid leaching of laterite nickel ore has been widely reported. Chinese patent application (CN116875759A) discloses a resource recovery method for recovering iron from high-pressure leaching residue of laterite nickel ore, wherein the high-pressure leaching residue of laterite nickel ore and a binder are mixed and stirred, and pellets are obtained through a pelletizing process, and dried to obtain dry pellets; the dry pellets are mixed with pyrite, and heated and roasted in an oxygen atmosphere to obtain roasted material and flue gas, and the flue gas is subjected to an acid-making process to obtain sulfuric acid; the roasted material, flux and reducing agent are mixed, and then heated and smelted to obtain molten iron, smelting slag and flue gas. Chinese patent application (CN119265405A) discloses a method for recovering leaching residue of laterite nickel ore, wherein the leaching residue of laterite nickel ore is roasted in the presence of a first reducing agent to obtain roasted sand and sulfur-containing tail gas; the roasted sand obtained above is smelted in the presence of a second reducing agent to obtain molten iron, smelting slag and coal gas. Chinese patent application (CN118326154A) discloses a comprehensive recycling method for all components of high-pressure acid leaching residue of laterite nickel ore, wherein the high-pressure acid leaching residue of laterite nickel ore, a binder and a reducing agent are mixed to form a pellet; the pellet is dried, then calcined with limestone to obtain a calcined material; the calcined material is smelted to obtain molten iron and hot slag; the molten iron is prepared into an iron ingot, and the hot slag is sequentially subjected to tempering, melting homogenization, molding, crystallization, and annealing to obtain microcrystalline glass. Chinese patent (CN117403057B) discloses a treatment method and active material of acid leaching residue of laterite nickel ore, wherein the acid leaching residue of laterite nickel ore, a regulating material, a fluxing material and a reducing agent are mixed and pressed to obtain a preform; the preform is roasted to obtain hot slag and hot flue gas, and the hot flue gas is used to make acid; the hot slag is magnetically separated to obtain refined iron material and tailings; the tailings, active material and exciting material are mixed and ground to obtain active materials.

[0004] In the technical route of smelting and recovering iron, the existing public technology mainly adopts oxidation or reduction roasting to pre-treat the acid leaching slag of laterite nickel ore, but the roasted materials obtained by such technical means have low mechanical strength and poor metallurgical properties, and cannot be used as the charge for large-scale, mature and reliable blast furnace ironmaking process. In the recovery of sulfur dioxide, due to the large flue gas flow rate and low concentration, the conventional roasting process often requires the introduction of sulfur sources into the raw materials or the re-enrichment of sulfur in the flue gas to meet the conditions for acid production, and the overall recovery of the acid production process is difficult. In the recovery of chemical components such as calcium, silicon, aluminum, and magnesium, the preparation of microcrystalline glass requires multiple high-temperature treatments and is limited in large-scale application. In the method of directly preparing active materials from magnetic separation tailings, the magnetic separation tailings have not been melted and quenched, and have no direct activity, requiring external active materials as active sources.

[0005] In summary, it is of great significance to develop a method for large-scale and efficient comprehensive utilization of all components of leaching residue from high-pressure acid leaching of laterite nickel ore. Summary of the invention

[0006] In view of the technical problems existing in the resource utilization of leaching residues from high-pressure acid leaching of laterite nickel ore in the prior art, the main purpose of the present invention is to provide a method for large-scale and efficient comprehensive utilization of all components of leaching residues from high-pressure acid leaching of laterite nickel ore (including acid leaching residues, iron and aluminum removal residues and neutralization tailings, etc.), so as to solve the problems of low efficiency and high consumption, low comprehensive recovery rate and difficulty in large-scale industrial application in the treatment of leaching residues from high-pressure acid leaching of laterite nickel ore in the prior art.

[0007] In order to achieve the above technical purpose, the present invention provides a method for comprehensive utilization of all components of leached residues from a high-pressure acid leaching process of laterite nickel ore, the method comprising the following steps: (1) pelletizing and sintering the iron-containing slag from the high-pressure acid leaching process of laterite nickel ore with raw materials including coke powder, flux and return ore to obtain sintered ore and sulfur dioxide flue gas; (2) using the sulfur dioxide flue gas to prepare sulfuric acid, and returning the obtained sulfuric acid to the high-pressure acid leaching process of laterite nickel ore; (3) smelting the sintered ore, coke and slag conditioning agent in a blast furnace to obtain molten iron and slag; The slag adjusting agent is used to control the CaO / SiO2 in the slag to be 1.0-1.5, the Al2O3 / SiO2 to be 0.1-0.6, the Al2O3 content to be 8-15wt%, the MgO content to be 5-12wt%, the Fe2O3 content to be less than 5wt%, and the S content to be less than 1.5wt%; The slag conditioning agent includes at least one of limestone, silica, dolomite and ferrous bauxite; (4) quenching the slag to obtain granulated slag; grinding a portion of the granulated slag to obtain granulated slag powder; (5) The granulated slag powder, the granulated slag and auxiliary materials including an alkali activator and tailings from a high-pressure acid leaching process of laterite nickel ore are mixed as backfill.

[0008] The key to the technical solution of the present invention is to realize the comprehensive resource utilization of three kinds of waste slags, namely, acid leaching slag, iron-removing aluminum slag, and neutralization tailings, produced by the high-pressure acid leaching process of laterite nickel ore. Based on the composition characteristics of the three kinds of waste slags, targeted differentiated treatment is carried out, and a three-stage conversion process path of "slag element recovery-slag activity regulation-tailings harmless backfilling" is proposed. For acid leaching slag and iron-removing aluminum slag, which contain rich iron and a large amount of silicon, aluminum, calcium, magnesium, sulfur and other components, the sulfur and iron elements therein can be efficiently recovered through the "sintering-blast furnace smelting" process route, and the composition of blast furnace slag is precisely adjusted, and cold quenching and grinding processes are combined to obtain granulated slag aggregate and high-activity granulated slag powder, giving the slag unique recycling characteristics. On this basis, granulated slag powder, granulated slag and neutralization tailings are used as the main components to construct a low-cost, high-performance backfill body, realizing "slag treatment with slag" and 100% resource utilization of slag.

[0009] The present invention uses a slag adjusting agent to adjust the composition of blast furnace smelting slag, for example, adjusting the basicity (CaO / SiO2) to 1.0-1.5, the activation coefficient (Al2O3 / SiO2) to 0.1-0.6, the Al2O3 content to 8-15wt%, the MgO content to 5-12wt%, the Fe2O3 content to less than 5wt%, and the S content to less than 1.5wt%. If the alkalinity is too strong, it is easy to cause the gel reaction to be too fast, resulting in uncontrolled early coagulation and uneven gel structure, which in turn affects the later strength and durability. If the alkalinity is too low, it may be insufficiently activated. If the activity coefficient is too high, it will disrupt the ideal ratio of aluminosilicate gel, affecting mechanical properties and chemical corrosion resistance. If the activity coefficient is too low, it will be unfavorable for colloid generation. If the Al2O3 content is too high, it may cause excessive aluminum content in the gel, forming an unstable phase and weakening durability. If the content is too low, the gelation reaction activity will be reduced. If the MgO content is too high, it is easy to promote the formation of expansive phases, increasing the risk of volume instability. If the MgO content is too low, it may lead to insufficient reaction activity. If the Fe2O3 content is too high, it will promote the formation of impurities, interfere with the formation of favorable gel structures, and reduce overall reactivity. If the S content is too high, it is easy to form excessive sulfates, inducing expansion, cracking and reduced durability. In summary, the present invention is conducive to obtaining backfill with better performance by regulating the slag phase.

[0010] As a preferred solution, the iron-containing slag from the high-pressure acid leaching process of laterite nickel ore includes high-pressure acid leaching slag from laterite nickel ore and / or iron- and aluminum-removing slag from high-pressure acid leaching liquid of laterite nickel ore.

[0011] As a preferred solution, the raw materials include the following components in percentage by weight: 50-75% iron-containing slag from high-pressure acid leaching of laterite nickel ore, 4-9% coke powder, 5-15% flux, and 15-30% return ore, wherein each raw material component is measured on a dry basis. A suitable ratio composition helps to optimize the sintering process, ensure the production and quality of sintered ore, and facilitate the smooth operation of the blast furnace. The flux is, for example, quicklime.

[0012] As a preferred solution, the sintering temperature is 1200-1400°C.

[0013] The present invention uses iron-containing slag from high-pressure acid leaching of laterite nickel ore as the iron raw material, and by matching sintering auxiliary materials such as coke powder, flux, and return ore, and at a suitable sintering temperature, a high-quality sintered ore can be obtained, for example, the total iron (TFe) content of the sintered ore is greater than 52wt%, the drum strength (TI) is greater than 60%, the reduction degree (RI) is greater than 65%, and the sulfur content is less than 0.2wt%. The obtained sintered ore is fully suitable for blast furnace ironmaking process. Sufficient total iron content, good mechanical strength and reducibility are crucial to the energy efficiency and operation stability of blast furnace ironmaking process. However, too high sulfur content in the sintered ore will directly increase the total sulfur content entering the furnace, causing the desulfurization load to increase and deteriorate the quality of molten iron.

[0014] As a preferred solution, the sulfur dioxide flue gas is the flue gas in the 50% to 100% area along the direction of travel of the sintering machine trolley, and its average sulfur dioxide concentration is higher than 1vol%. During the sintering process, the sulfur in the iron-containing slag of the high-pressure acid leaching process of laterite nickel ore is converted into sulfur dioxide, and moves downward with the airflow and is absorbed by the moisture and flux in the lower sintering mixture. When the over-wet zone reaches the bottom and gradually disappears, the sulfur dioxide is desorbed and released in a concentrated manner. Therefore, the appropriate flue area position is the key to obtaining high-quality sulfur dioxide. A sulfur dioxide concentration of more than 1vol% is conducive to maintaining self-heating balance in acid production processes (such as the Conkaite process).

[0015] As a preferred solution, the particle size range of the granulated slag is 1 to 10 mm, and the glass content is higher than 85wt%. Granulated slag is mainly used as aggregate for backfilling material, and has a high glass content and a particle size range of 1 to 10 mm. Too large particles will reduce its specific surface area and reduce the reaction interface with the alkali-activated gelling system, thereby affecting the formation of the gel phase and the bonding between the aggregate and the colloid. This will cause the material density to decrease and the porosity to increase, thereby weakening the early strength and durability, and may also affect the fluidity and overall uniformity of the construction. It is further preferred that the particle size range of the granulated slag is 1 to 5 mm. The glass content is too low and the proportion of the crystalline phase increases, which directly leads to low activity of the subsequent granulated slag powder, affecting the density and durability of the microstructure of the filler.

[0016] As a preferred solution, the specific surface area of ​​the granulated slag powder is 400-700 kg / m 2 , the particle size D50=8~15μm, and D90 is less than 45μm, and the moisture content is less than 1 wt%. Granulated slag powder is mainly used as a cementitious active ingredient. If its specific surface area is too low, the reaction interface is insufficient and the activity is reduced; if its specific surface area is too high, it may increase the water demand and affect the construction performance. Coarse particles (D50 greater than 15μm or D90 over 45μm) will lead to uneven reaction, reduce the early reaction rate and the overall cementation effect. Too high a moisture content is prone to prehydration, affecting storage stability and alkali-induced reaction control. Granulated slag powder is obtained by grinding granulated slag, and the grinding process is a combination of any one or more grinding methods of ball milling, high-pressure roller milling and vertical milling.

[0017] As a preferred solution, the alkaline activator includes at least one of NaOH, KOH, Na2CO3, and Na2SiO3. These alkaline activators are conventional reagents in the industry.

[0018] As a preferred solution, the backfill material comprises the following components in mass percentage: 25-50% granulated slag powder; 3-10% alkali activator; 20-40% granulated slag; 10-25% neutralized tailings from high pressure acid leaching of laterite nickel ore. The neutralized tailings contain a large amount of calcium sulfate salt components, which can work together with the alkali activator (such as NaOH or sodium silicate) to promote the hydration reaction of the cementitious material and accelerate the formation of hydration products such as ettringite, thereby improving the early strength of the material.

[0019] As a preferred solution, the backfill material contains no more than 15 wt % of admixture.

[0020] As a preferred solution, the admixture includes at least one of fly ash, metakaolin and lime. The addition of an appropriate amount of admixture is beneficial to reducing the defects of a single gel phase and further enhancing the overall stability of the backfill material.

[0021] As a preferred solution, the backfill material is mixed with water at a water-binder ratio of 0.25-0.4, and then filled and cured. Under standard curing conditions, the compressive strength of the backfill material after 7 days and 28 days is higher than 3MPa and 8MPa respectively.

[0022] Compared with the prior art, the technical solution of the present invention has the following beneficial technical effects:

[0023] 1. The present invention specifically sintered and agglomerated the acid leaching slag with high iron content and the iron-removing aluminum slag in the leaching slag of the high-pressure acid leaching process of laterite nickel ore to obtain high-quality furnace charge suitable for blast furnace ironmaking, and combined with the sintering process principle and the concentrated emission characteristics of sintering flue gas, it realizes the deep separation of iron and sulfur elements, and at the same time completes the enrichment of sulfur elements, creating conditions for low-cost self-heating balance acid production, and the sulfuric acid cycle is used in the leaching process of the high-pressure acid leaching process of laterite nickel ore, which significantly reduces the outsourcing cost of sulfuric acid raw materials for the high-pressure acid leaching process. In addition, the waste heat generated by the three major links of sintering, acid production, and blast furnace smelting can be used to prepare steam for the slurry preheating process of the high-pressure acid leaching process of laterite nickel ore, significantly reducing the demand for additional heat in this link, thereby reducing energy consumption costs.

[0024] 2. The present invention makes full use of the characteristics of the mineral composition of the three types of waste slags, namely, acid leaching slag, iron and aluminum removal slag, and neutralization tailings, produced by the high-pressure acid leaching process of laterite nickel ore, and realizes the recovery of useful elements and mineral conversion in various waste slags based on a special process path, and designs a unique backfill material formula. By precisely adjusting the composition of blast furnace slag, combined with cold quenching to prepare granulated slag with high glass content, and further grinding to obtain granulated slag powder, the granulated slag has a coarse particle size and low activity, and the granulated slag powder has a fine particle size and high activity. With the reasonable combination of slag powder and slag, the different reaction rates (slag powder's early rapid reaction and slag's long-term sustained release effect) and physical properties (slag powder improves density, slag optimizes fluidity) of the two complement each other, which helps to provide balanced performance improvement for backfill materials at different stages (early and long-term), while optimizing the workability and construction performance of the backfill materials.

[0025] 3. The process system of the present invention has a high degree of integration and can achieve full-chain coordination of high-pressure acid leaching-sintering-smelting-cementitious material preparation. It effectively integrates the leaching slag itself of the high-pressure acid leaching process of laterite nickel ore and the additional waste generated in the comprehensive recycling process, completes "element recovery" and "slag treatment with slag", realizes 100% resource utilization of slag, obtains economic benefits and simultaneously eliminates the negative impact of slag storage or landfill treatment on the environment, reflecting the concept of green development.

[0026] In summary, the technology of the present invention has the potential for industrial promotion, especially in the field of large-scale treatment of leached residue from high-pressure acid leaching of laterite nickel ore, which will form a significant competitive advantage. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The present invention is a process flow chart of the comprehensive utilization method of all components of leached slag from laterite nickel ore high pressure acid leaching process. DETAILED DESCRIPTION

[0028] The present invention is further described in detail below in conjunction with preferred implementation examples, but is not intended to limit the protection scope of the claims of the present invention.

[0029] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0030] Example 1

[0031] The sintering raw material ratio is carried out according to the mass percentage (dry basis), and the binary basicity is set at 1.6 and the granulation moisture is 17.5. The mass ratios of laterite nickel ore high-pressure iron-containing slag (80wt% acid leaching slag + 20wt% iron-aluminum slag), coke powder, flux (quicklime), and return ore (internal) are 58.2%, 8.0%, 10.7%, and 23.1%, respectively. The subsequent granulation is carried out and sintered in the sintering cup. At the same time, the flue gas analyzer is used to test and analyze the flue gas online. The final sintering time is 40.52min. The indicators of the sintered ore are as follows: total iron content (TFe) 52.2wt%, drum strength (TI) 62.7%, reduction degree (RI) 65.8%, and sulfur content 0.1wt%. The average concentration of sulfur dioxide in the flue gas from 20 to 40 minutes of sintering is 1.4vol%, which meets the acid production conditions of the wet process. The obtained sintered ore is matched with coke and slag regulator, smelted in a high-temperature box-type resistance furnace (about 1500℃) and slag-iron separation is achieved (the density difference between slag and iron is self-stratified), and then water quenching is performed to finally obtain iron blocks and slag. The slag basicity (CaO / SiO2) is 1.2, the activation coefficient (Al2O3 / SiO2) is 0.55, the Al2O3 content is 14.4wt%, the MgO content is 8.3wt%, the Fe2O3 content is 1.1wt%, and the S content is 0.71wt%. It is then crushed by rollers to obtain granulated slag, which has a glass content of 91wt% and an average particle size of 4.8mm. 50% of the granulated slag is ground by a ball mill to obtain granulated slag powder, which has a specific surface area of ​​530kg / m², a median particle size (D50) of 11.1μm, a 90% particle size (D90) of 38.7μm, and a moisture content of 0.32wt%. 35wt% granulated slag powder, 7wt% fly ash, 35wt% granulated slag, and 16wt% neutralized tailings were dry mixed with a powerful mixer to obtain a dry mixture; at the same time, 7wt% alkali activator (50wt% NaOH+50wt% Na2SiO3) was dissolved in water to obtain an alkali activator solution, in which the water-binder ratio was controlled to be 0.35; finally, the alkali activator solution was slowly added to the dry mixture, and vigorously stirred again to obtain backfill. The backfill was poured into a mold for molding, and cured for 7 days and 28 days under standard curing conditions (temperature 20±2℃, relative humidity above 95%), and its compressive strength was tested. The main components and compositions of acid leaching slag, iron-aluminum slag and neutralized tailings are shown in Table 1.

[0032] In this embodiment, under standard curing conditions, the 7-day and 28-day compressive strengths of the obtained backfill material are 4.2 MPa and 13.9 MPa, respectively, which meet the requirements of mine backfill engineering.

[0033] Example 2

[0034] The sintering raw material ratio is carried out according to the mass percentage (dry basis), and the binary basicity is set at 1.6 and the granulation moisture is 17.5. The mass ratios of high-pressure iron-containing slag of laterite nickel ore (80wt% acid leaching slag + 20wt% iron-aluminum slag), coke powder, flux (quicklime), and return ore (internal) are 58.2%, 8.0%, 10.7%, and 23.1%, respectively. The subsequent granulation is carried out and sintered in a sintering cup. At the same time, the flue gas analyzer is used to test and analyze the flue gas online. The final sintering time is 40.52min. The indicators of the sintered ore are as follows: total iron content (TFe) 52.2wt%, drum strength (TI) 62.7%, reduction degree (RI) 65.8%, and sulfur content 0.1wt%. The average concentration of sulfur dioxide in the flue gas from 24 to 36 minutes of sintering is 2.1vol%, reaching the acid production conditions of the wet process. The obtained sintered ore is matched with coke and slag regulator, smelted in a high-temperature box-type resistance furnace (about 1500℃) and slag-iron separation is achieved (slag and iron density difference are separated by themselves), and then water quenching is performed to finally obtain iron blocks and slag. The slag basicity (CaO / SiO2) is 1.1, the activation coefficient (Al2O3 / SiO2) is 0.3, the Al2O3 content is 8.9wt%, the MgO content is 6.6wt%, the Fe2O3 content is 0.8wt%, and the S content is 0.65wt%. It is then crushed by rollers to obtain granulated slag, which has a glass content of 94wt% and an average particle size of 3.3mm. 40% of the granulated slag is ground by a ball mill to obtain granulated slag powder, which has a specific surface area of ​​610 kg / m², a median particle size (D50) of 8.9μm, a 90% particle size (D90) of 33.4μm, and a moisture content of 0.25wt%. 26wt% granulated slag powder, 13wt% fly ash, 37wt% granulated slag, and 19wt% neutralized tailings were dry mixed with a powerful mixer to obtain a dry mixture; at the same time, 5wt% alkali activator (50wt% NaOH+50wt% Na2SiO3) was dissolved in water to obtain an alkali activator solution, in which the water-binder ratio was controlled to be 0.38; finally, the alkali activator solution was slowly added to the dry mixture, and vigorously stirred again to obtain backfill. The backfill was poured into a mold for molding, and cured for 7 days and 28 days under standard curing conditions (temperature 20±2℃, relative humidity above 95%), and its compressive strength was tested. The main components and composition of acid leaching slag, iron-aluminum slag and neutralized tailings are shown in Table 1.

[0035] In this embodiment, under standard curing conditions, the 7-day and 28-day compressive strengths of the obtained backfill material are 3.4 MPa and 15.7 MPa, respectively, which meet the requirements of mine backfill engineering.

[0036] Example 3

[0037] The sintering raw material ratio is carried out according to the mass percentage (dry basis), and the binary basicity is set at 1.6 and the granulation moisture is 17.5. The mass ratios of high-pressure iron-containing slag of laterite nickel ore (80wt% acid leaching slag + 20wt% iron-aluminum slag), coke powder, flux (quicklime), and return ore (internal) are 58.2%, 8.0%, 10.7%, and 23.1%, respectively. The subsequent granulation is carried out and sintered in a sintering cup. At the same time, the flue gas analyzer is used to test and analyze the flue gas online. The final sintering time is 40.52min. The indicators of the sintered ore are as follows: total iron content (TFe) 52.2wt%, drum strength (TI) 62.7%, reduction degree (RI) 65.8%, and sulfur content 0.1wt%. The average concentration of sulfur dioxide in the flue gas from 26 to 34 minutes of sintering is 3.8vol%, reaching the acid production conditions of the wet process. The obtained sintered ore is matched with coke and slag regulator, smelted in a high-temperature box-type resistance furnace (about 1500℃) and slag-iron separation is achieved (slag and iron density difference are self-stratified), followed by water quenching and cooling, and finally iron blocks and slag are obtained. The slag basicity (CaO / SiO2) is 1.3, the activation coefficient (Al2O3 / SiO2) is 0.4, the Al2O3 content is 11.8wt%, the MgO content is 11.5wt%, the Fe2O3 content is 1.2wt%, and the S content is 0.82wt%. It is then crushed by rollers to obtain granulated slag, which has a glass content of 89wt% and an average particle size of 6.5mm. 70% of the granulated slag is ground by a ball mill to obtain granulated slag powder, which has a specific surface area of ​​450 kg / m², a median particle size (D50) of 13.4μm, a 90% particle size (D90) of 42.7μm, and a moisture content of 0.27wt%. 43.5wt% granulated slag powder, 2wt% fly ash, 21.5wt% granulated slag, and 24wt% neutralized tailings were dry mixed with a powerful mixer to obtain a dry mixture; at the same time, 9wt% alkali activator (50wt% NaOH + 50wt% Na2SiO3) was dissolved in water to obtain an alkali activator solution, in which the water-binder ratio was controlled to be 0.31; finally, the alkali activator solution was slowly added to the dry mixture, and vigorously stirred again to obtain backfill. The backfill was poured into a mold for molding, and cured for 7 days and 28 days under standard curing conditions (temperature 20±2℃, relative humidity above 95%), and its compressive strength was tested. The main components and compositions of acid leaching slag, iron-aluminum slag and neutralized tailings are shown in Table 1.

[0038] In this embodiment, under standard curing conditions, the 7-day and 28-day compressive strengths of the obtained backfill material are 5.1 MPa and 11.3 MPa, respectively, which meet the requirements of mine backfill engineering.

[0039] Comparative Example 1

[0040] The sintering raw material ratio is carried out according to the mass percentage (dry basis), the binary basicity is set at 1.6, and the granulation moisture is 17.5. The mass ratios of laterite nickel ore high-pressure iron-containing slag (80wt% acid leaching slag + 20wt% iron-aluminum slag), coke powder, flux (quicklime), and return ore (internal) are 58.2%, 8.0%, 10.7%, and 23.1%, respectively. The subsequent granulation is carried out and sintered in the sintering cup. At the same time, the flue gas analyzer is used to test and analyze the flue gas online. The final sintering time is 40.52min. The indicators of the sintered ore are as follows: total iron content (TFe) 52.2wt%, drum strength (TI) 62.7%, reduction degree (RI) 65.8%, and sulfur content 0.1wt%. The average concentration of sulfur dioxide in the flue gas from 0 to 40.52 minutes of sintering is 0.6 vol%. The recovery is difficult due to the low concentration, and it is necessary to enrich and concentrate or add sulfur and heat, which is costly. There is no effective direct self-heating equilibrium acid production process. The main components and compositions of acid leaching slag, iron-aluminum slag and neutralization tailings are shown in Table 1.

[0041] Comparative Example 2

[0042] The sintering raw material ratio is carried out according to the mass percentage (dry basis), and the binary basicity is set at 1.6 and the granulation moisture is 17.5. The mass ratios of high-pressure iron-containing slag of laterite nickel ore (80wt% acid leaching slag + 20wt% iron-aluminum slag), coke powder, flux (quicklime), and return ore (internal) are 58.2%, 8.0%, 10.7%, and 23.1%, respectively. The subsequent granulation is carried out and sintered in a sintering cup. At the same time, the flue gas analyzer is used to test and analyze the flue gas online. The final sintering time is 40.52min. The indicators of the sintered ore are as follows: total iron content (TFe) 52.2wt%, drum strength (TI) 62.7%, reduction degree (RI) 65.8%, and sulfur content 0.1wt%. The average concentration of sulfur dioxide in the flue gas from 20 to 40 minutes of sintering is 1.4vol%, which meets the acid production conditions of the wet process. The obtained sintered ore is matched with coke and slag adjusting agent, smelted in a high temperature box-type resistance furnace (about 1500 ° C) and slag iron separation is achieved (slag and iron density difference are self-layered), followed by water quenching and cooling, and finally iron blocks and slag are obtained. Slag basicity (CaO / SiO2) 0.9, activation coefficient (Al2O3 / SiO2) 0.65, Al2O3 content 16.3wt%, MgO content 4.3wt%, Fe2O3 content 6.9wt%, S content 0.67wt%. The backfill material is subsequently obtained by the same process route and formula as Example 1, and the backfill material is poured into a mold for molding, and cured for 7 days and 28 days under standard curing conditions (temperature 20 ± 2 ° C, relative humidity above 95%), and its compressive strength is tested. The main components and composition of acid leaching slag, iron-aluminum slag and neutralization tailings are shown in Table 1.

[0043] In this comparative example, under standard curing conditions, the 7-day and 28-day compressive strengths of the obtained backfill material were 1.7MPa and 5.3MPa, respectively, which could not meet the requirements of mine backfill engineering. Due to the low slag basicity (CaO / SiO2), the high activation coefficient (Al2O3 / SiO2), the excessive content of Al2O3 (16.3wt%) and Fe2O3 (6.9wt%), and the insufficient MgO content (4.3wt%), the reaction system was unbalanced, the formation of favorable colloidal phase was inhibited, and the activity of the cementitious material was significantly reduced.

[0044] Comparative Example 3

[0045] The sintering raw material ratio is carried out according to the mass percentage (dry basis), and the binary basicity is set at 1.6 and the granulation moisture is 17.5. The mass ratios of high-pressure iron-containing slag of laterite nickel ore (80wt% acid leaching slag + 20wt% iron-aluminum slag), coke powder, flux (quicklime), and return ore (internal) are 58.2%, 8.0%, 10.7%, and 23.1%, respectively. The subsequent granulation is carried out and sintered in a sintering cup. At the same time, the flue gas analyzer is used to test and analyze the flue gas online. The final sintering time is 40.52min. The indicators of the sintered ore are as follows: total iron content (TFe) 52.2wt%, drum strength (TI) 62.7%, reduction degree (RI) 65.8%, and sulfur content 0.1wt%. The average concentration of sulfur dioxide in the flue gas from 20 to 40 minutes of sintering is 1.4vol%, which meets the acid production conditions of the wet process. The obtained sintered ore is matched with coke and slag regulator, smelted in a high-temperature box-type resistance furnace (about 1500℃) and slag-iron separation is achieved (slag and iron density difference are self-stratified), and then naturally cooled to finally obtain iron blocks and slag. The slag basicity (CaO / SiO2) is 1.1, the activation coefficient (Al2O3 / SiO2) is 0.3, the Al2O3 content is 8.9wt%, the MgO content is 6.6wt%, the Fe2O3 content is 0.8wt%, and the S content is 0.53wt%. It is then crushed by rollers to obtain granulated slag, which has a glass content of 54wt% and an average particle size of 7.6mm. 40wt% of the granulated slag is ground by a ball mill to obtain granulated slag powder, which has a specific surface area of ​​350 kg / m², a median particle size (D50) of 17.8μm, a 90% particle size (D90) of 52.4μm, and a moisture content of 0.45wt%. Subsequently, the same process route and formula as in Example 2 were used to obtain the backfill material, which was poured into a mold for molding, and cured for 7 days and 28 days under standard curing conditions (temperature 20±2°C, relative humidity above 95%), and its compressive strength was tested. The main components and compositions of the acid leaching residue, iron-aluminum residue and neutralization tailings are shown in Table 1.

[0046] In this comparative example, under standard curing conditions, the 7-day and 28-day compressive strengths of the obtained backfill material are 0.5MPa and 4.8MPa, respectively, which cannot meet the requirements of mine backfill engineering. The higher the glass content of the granulated slag, the greater the potential activity, while the low natural cooling rate leads to a decrease in the glass content, which in turn affects the activity of the slag. In addition, because the granulated slag powder particles are too coarse, the hydration reaction of the coarse particles is slow, resulting in insufficient generation of hydration products, affecting the improvement of early strength. At the same time, the granulated slag powder that is too coarse may increase the porosity of the cementitious material and reduce its compactness, thereby affecting long-term durability.

[0047] Comparative Example 4

[0048] The sintering raw material ratio is carried out according to the mass percentage (dry basis), and the binary basicity is set at 1.6 and the granulation moisture is 17.5. The mass ratios of high-pressure iron-containing slag of laterite nickel ore (80wt% acid leaching slag + 20wt% iron-aluminum slag), coke powder, flux (quicklime), and return ore (internal) are 58.2%, 8.0%, 10.7%, and 23.1%, respectively. The subsequent granulation is carried out and sintered in a sintering cup. At the same time, the flue gas analyzer is used to test and analyze the flue gas online. The final sintering time is 40.52min. The indicators of the sintered ore are as follows: total iron content (TFe) 52.2wt%, drum strength (TI) 62.7%, reduction degree (RI) 65.8%, and sulfur content 0.1wt%. The average concentration of sulfur dioxide in the flue gas from 20 to 40 minutes of sintering is 1.4vol%, which meets the acid production conditions of the wet process. The obtained sintered ore is matched with coke and slag regulator, smelted in a high-temperature box-type resistance furnace (about 1500℃) and slag and iron are separated, and then water quenching is performed to finally obtain iron blocks and slag. The slag basicity (CaO / SiO2) is 1.3, the activation coefficient (Al2O3 / SiO2) is 0.4, the Al2O3 content is 11.8wt%, the MgO content is 11.5wt%, the Fe2O3 content is 1.2wt%, and the S content is 0.97wt%. It is then crushed by rollers to obtain granulated slag, which has a glass content of 88wt% and an average particle size of 6.5mm. 100% of the granulated slag is ground in a ball mill to obtain granulated slag powder, which has a specific surface area of ​​450 kg / m², a median particle size (D50) of 13.4μm, a 90% particle size (D90) of 42.7μm, and a moisture content of 0.27wt%. 65wt% granulated slag powder, 2wt% fly ash, and 24wt% neutralized tailings were dry mixed with a powerful mixer to obtain a dry mixture; at the same time, 9wt% alkali activator (50wt% NaOH + 50wt% Na2SiO3) was dissolved in water to obtain an alkali activator solution, in which the water-binder ratio was controlled to be 0.37; finally, the alkali activator solution was slowly added to the dry mixture, and vigorously stirred again to obtain backfill. The backfill was poured into a mold for molding, and cured for 7 days and 28 days under standard curing conditions (temperature 20±2℃, relative humidity above 95%), and its compressive strength was tested. The main components and composition of acid leaching slag, iron-aluminum slag and neutralized tailings are shown in Table 1.

[0049] In this embodiment, under standard curing conditions, the 7-day and 28-day compressive strengths of the obtained backfill material are 3.9 MPa and 7.2 MPa, respectively, which cannot meet the requirements of mine backfill engineering.

[0050] .

Claims

1. A method for comprehensive utilization of all components of leached residues from high pressure acid leaching of laterite nickel ore, characterized in that: The following steps are involved: (1) pelletizing and sintering the iron-containing slag from the high-pressure acid leaching process of laterite nickel ore with raw materials including coke powder, flux and return ore to obtain sintered ore and sulfur dioxide flue gas; (2) using the sulfur dioxide flue gas to prepare sulfuric acid, and returning the obtained sulfuric acid to the high-pressure acid leaching process of laterite nickel ore; (3) smelting the sintered ore, coke and slag conditioning agent in a blast furnace to obtain molten iron and slag; The slag adjusting agent is used to control the CaO / SiO2 in the slag to be 1.0-1.5, the Al2O3 / SiO2 to be 0.1-0.6, the Al2O3 content to be 8-15wt%, the MgO content to be 5-12wt%, the Fe2O3 content to be less than 5wt%, and the S content to be less than 1.5wt%; The slag conditioning agent includes at least one of limestone, silica, dolomite and ferrous bauxite; (4) quenching the slag to obtain granulated slag; grinding a portion of the granulated slag to obtain granulated slag powder; (5) The granulated slag powder, the granulated slag and auxiliary materials including an alkali activator and tailings from a high-pressure acid leaching process of laterite nickel ore are mixed as backfill.

2. The method for comprehensive utilization of all components of leached residues from a high-pressure acid leaching process of laterite nickel ore according to claim 1, characterized in that: The iron-containing slag from the high-pressure acid leaching process of laterite nickel ore includes high-pressure acid leaching slag from laterite nickel ore and / or iron-removal aluminum slag from neutralization of high-pressure acid leaching liquid of laterite nickel ore; and / or, The raw materials include the following components in percentage by weight: 50-75% iron-containing slag from high-pressure acid leaching of laterite nickel ore, 4-9% coke powder, 5-15% flux, and 15-30% return ore, wherein each raw material component is measured on a dry basis.

3. The method for comprehensive utilization of all components of leached residues from a high-pressure acid leaching process of laterite nickel ore according to claim 1 or 2, characterized in that: The sintering temperature is 1200-1400°C.

4. The method for comprehensive utilization of all components of leached residues from a high-pressure acid leaching process of laterite nickel ore according to claim 1, characterized in that: The sulfur dioxide flue gas is flue gas in the area of ​​50% to 100% along the traveling direction of the sintering machine trolley, and its average sulfur dioxide concentration is higher than 1 vol%.

5. The method for comprehensive utilization of all components of leached residues from a high-pressure acid leaching process of laterite nickel ore according to claim 1, characterized in that: The granulated slag has a particle size range of 1-10 mm and a glass content higher than 85 wt %.

6. The method for comprehensive utilization of all components of leached residues from high pressure acid leaching of laterite nickel ore according to claim 1, characterized in that: The specific surface area of ​​the granulated slag powder is 400-700 kg / m 2 The particle size D50 of the particles is 8~15μm, and D90 is less than 45μm, and the water content is less than 1 wt%.

7. The method for comprehensive utilization of all components of leached residues from high pressure acid leaching of laterite nickel ore according to claim 1, characterized in that: The alkaline activator includes at least one of NaOH, KOH, Na2CO3, and Na2SiO3.

8. The method for comprehensive utilization of all components of leached residues from high pressure acid leaching of laterite nickel ore according to claim 1, 5, 6 or 7, characterized in that: The backfill material comprises the following components in percentage by weight: 25-50% granulated slag powder; 3-10% alkali activator; 20-40% granulated slag; and 10-25% tailings from high pressure acid leaching process of laterite nickel ore.

9. The method for comprehensive utilization of all components of leached residues from high pressure acid leaching of laterite nickel ore according to claim 8, characterized in that: The backfill material contains no more than 15 wt % of admixture.

10. The method for comprehensive utilization of all components of leached residues from high pressure acid leaching of laterite nickel ore according to claim 9, characterized in that: The admixture includes at least one of fly ash, metakaolin and lime.

Citation Information

Patent Citations

  • Resource recycling method for recycling iron from laterite-nickel ore high-pressure leaching residues

    CN116875759A

  • Treatment method of laterite nickel ore acid leaching residue, active materials

    CN117403057B

  • Method for sintering and blending nickel laterite ore

    CN104152676A

  • Treatment method and equipment for laterite-nickel ore leaching residues

    CN116949282A

  • Method for high value-added utilization of laterite-nickel ore high-pressure acid leaching residues

    CN117286334A

Cited By

  • Method for recovering nickel and cobalt from laterite-nickel ore

    CN120818698A

  • Laterite-nickel ore leaching residue treatment process

    CN120818699A

  • A process for treating laterite nickel ore leach residue

    CN120818699B